The Surficial Basin Sediment Investigation and Its Concerned Vertebrate Fossils in Sirtwo Island, Western Part of Saguling Dam, West Java, Indonesia - Johan Budi Winarto; Wilda Aini Nurlathifah; Agustina Djafar; Andy Dharmedy Sipayung; Rahajeng Ayu Permana Sari; Halmi Insani (Indonesian Journal of Earth Sciences, 2022)
In October 2021, the depreciation of the water level of dam Saguling revealed the surficial sediment where was dam up Citarum river. Sirtwo island and surroundings are part of the body sediment were arisen which is part of the sedimentary facies in the western of Bandung Lake ancient. Several vertebrate fossils were found on Sirtwo island and Pasir Benteng island. The investigation of vertebrate fossils was carried out to understand where are deposited in Bandung lake. The geological survey lead to the recognition of types of lake deposits and was divided into 5 block observations i.e., Block A, Block B, Block C, Block D, and Block E. Geographic information system was used to determine the location points where the fossil was found and is correlated with other location. The fossils fragment is identified as vertebrate fossils i.e., Bovid sp., Rusa sp., and Elephas maximus. The detail of vertebrate fossils type and sediment petrology is under further analysis. The sedimentary facies are lake deposit and is distinguished into 3 sub-facies: 1) volcanic deposit with vertebrate fossil 2) sandstone tuff without vertebrate fossil and 3) sandstone tuff with vertebrate fossil. The age of lithology is estimated between 10.000 till >135.000 Years ago and the depositional environment is interpreted into fan lake, channel, and lake bottom. This study clearly determines lithofacies in the research area which contain vertebrate fossils.